How to cheat at designing a Windows Server 2003 Active Directory infrastructure - Meyer, Melissa M. (Rockland, MA : Syngress Press, 2006)
Windows 2003 Server is unquestionably the dominant enterprise level operating system in the industry, with 95% of all companies running it. And for the last tow years, over 50% of all product upgrades have been security related. Securing Windows Server, according to bill gates, is the company's #1 priority. The book will start off by teaching readers to create the conceptual design of their Active Directory infrastructure by gathering and analyzing business and technical requirements. Next, readers will create the logical design for an Active Directory infrastructure. Here the book starts to drill deeper and focus on aspects such as group policy design. Finally, readers will learn to create the physical design for an active directory and network Infrastructure including DNS server placement; DC and GC placements and Flexible Single Master Operations (FSMO) role placement. The next book in our best selling and critically acclaimed How to Cheat series. This is the perfect book for users who have already purchased How to Cheat at Managing Windows 2003 Small Business Server. * Active Directory is the market leader in the directory services space, and 57% of all Microsoft corporate customers have deployed AD * Follows Syngress's proven "How To Cheat" methodology * Companion Web site offers dozens of templates, "Cheat Sheets", and checklists for readers.
The assessment stage -- Developing the active directory infrastructure design -- Developing the network service design -- Designing the logical components -- Name resolution -- Remote access and address management -- Service sizing and placement -- The physical design.
Keywords: Directory services (Computer network technology).; Microsoft Windows server; Electronic books